2002
DOI: 10.1034/j.1600-0633.2002.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use and foraging success of 0+ pike (Esox lucius L.) in experimental ponds related to prey fish, water transparency and light intensity

Abstract: – This study investigated the habitat use of 0+ pike (9–17 cm) in relation to two different water transparency regimes (clear water/chlorophyll water), two different light regimes (day/night) and the presence/absence of prey using 16 m2 experimental ponds. Pike could freely choose between two structured habitats (a simple structured and a complex structured), an interface habitat (between the structured habitats and open water) and an open water habitat. Foraging success of the pike in relation to water transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…In a correlative study of 37 Canadian lakes, with Secchi depth comparable to the lakes of this study, Craig and Babaluk (1989) found that the condition factor of pike decreased with Secchi depth. Skov et al (2002) found no difference in pike condition or consumption rate in an experiment where 0+ pike were foraging on perch in reduced water transparency vs. a clear-water control. However, water transparency was here varied by changes in water colour, not turbidity.…”
Section: Lake Surveymentioning
confidence: 90%
“…In a correlative study of 37 Canadian lakes, with Secchi depth comparable to the lakes of this study, Craig and Babaluk (1989) found that the condition factor of pike decreased with Secchi depth. Skov et al (2002) found no difference in pike condition or consumption rate in an experiment where 0+ pike were foraging on perch in reduced water transparency vs. a clear-water control. However, water transparency was here varied by changes in water colour, not turbidity.…”
Section: Lake Surveymentioning
confidence: 90%
“…In contrast, the anti-predator behavior of juvenile fish, such as using macrophytes for refuge, may occur less frequently in turbid water, where hunting by sight-dependent predator fish is less successful (Abrahams and Kattenfeld 1997). Under clear-water conditions, juvenile pike (Esox ludus) spent more time foraging among complex structures compared to an even distribution between complexity and open water under turbid conditions (Skov et al 2002). In a survey of 33 interconnected shallow ponds, Cottenie et al (2001) found that zooplankton community structure depended strongly on predation intensity and macrophyte cover and that the clear-water state coincided with macrophytes, piscivorous fish and large Daphnia species.…”
mentioning
confidence: 98%
“…Although it is well recognized that vegetation is an essential component of Northern Pike habitat that provides spawning, feeding, rearing and cover opportunities (Witcomb 1965;Scott and Crossman 1973;Benson 1980;Bry 1996;Casselman 1996;Grimm and Klinge 1996;Skov and Berg 1999;Skov et al 2002;Skov and Koed 2004), vegetation that is extremely dense can be undesirable and can hinder the Northern Pikes' visual-based hunting tactics (Headrick and Carline 1993;Casselman and Lewis 1996). Further, Eklov (1997) found the size of Northern Pike is inversely related to vegetation density in oligotrophic lakes (i.e., pike fry occupy more densely vegetated areas than do adults).…”
Section: Discussionmentioning
confidence: 99%
“…Adult Northern Pike return to natal grounds in subsequent years to spawn (Frost and Kipling 1967;Raat 1988;Miller et al 2001). Y-O-Y Northern Pike remain in the vegetative cover and shallow water of these spawning sites (Inskip 1982;Skov et al 2002;Cucherousset et al 2009). In a recent study by Cucherousset et al (2009), it was found that Y-O-Y Northern Pike that had a mean fork length of 51 mm (slightly larger than the mean length collected in this study) moved within an average radial distance of only 14.3 m, and tended to hold in localized habitat patches.…”
Section: Effects Of Forest Fire On Young-of-the-year Northern Pike Ementioning
confidence: 99%